Changes in gene expression during female reproductive development in a color polymorphic insect. (1st June 2020) - Willink, Beatriz; Duryea, Mary Catherine; Wheat, Christopher; Svensson, Erik I.
Abstract: Pleiotropy (multiple phenotypic effects of single genes) and epistasis (gene interaction) have key roles in the development of complex phenotypes, especially in polymorphic taxa. The development of discrete and heritable phenotypic polymorphisms often emerges from major‐effect genes that interact with other loci and have pleiotropic effects on multiple traits. We quantified gene expression changes during ontogenetic color development in a polymorphic insect (damselfly: Ischnura elegans ), with three heritable female morphs, one being a male mimic. This female color polymorphism is maintained by male mating harassment and sexual conflict. Using transcriptome sequencing and de novo assembly, we demonstrate that all three morphs downregulate gene expression during early color development. The morphs become increasingly differentiated during sexual maturation and when developing adult coloration. These different ontogenetic trajectories arise because the male‐mimic shows accelerated (heterochronic) development, compared to the other female morphs. Many loci with regulatory functions in reproductive development are differentially regulated in the male‐mimic, including upstream and downstream regulators of ecdysone signaling and transcription factors potentially influencing sexual differentiation. Our results suggest that long‐term sexual conflict does not only maintain this polymorphism, but has also modulated the evolution of gene expression profiles during color development of these sympatric female morphs.